Protein tyrosine phosphatase PTPN22 regulates LFA-1 dependent Th1 responses - Sanchez-Blanco, C; Clarke, F; Cornish, G; Depoil, D; Thompson, S; Dai, X; Rawlings, D; Dustin, M; Zamoyska, R; Cope, A; Purvis, H (Elsevier, 2018)
A missense C1858T single nucleotide polymorphism within PTPN22 is a strong genetic risk factor for the development of multiple autoimmune diseases. PTPN22 encodes a protein tyrosine phosphatase that negatively regulates immuno-receptor proximal Src and Syk family kinases. Notably, PTPN22 negatively regulates kinases downstream of T-cell receptor (TCR) and LFA-1, thereby setting thresholds for T-cell activation. Alterations to the quality of TCR and LFA-1 engagement at the immune synapse and the regulation of downstream signals can have profound effects on the type of effector T-cell response induced. Here we describe how IFNγ+ Th1 responses are potentiated in Ptpn22−/− T-cells and in T-cells from mice expressing Ptpn22R619W (the mouse orthologue of the human genetic variant) as they age, or following repeated immune challenge, and explore the mechanisms contributing to the expansion of Th1 cells. Specifically, we uncover two LFA-1-ICAM dependent mechanisms; one T-cell intrinsic, and one T-cell extrinsic. Firstly, we found that in vitro anti-CD3/LFA-1 induced Th1 responses were enhanced in Ptpn22−/− T-cells compared to WT, whereas anti-CD3/anti-CD28 induced IFNy responses were similar. These data were associated with an enhanced ability of Ptpn22−/− T-cells to engage ICAM-1 at the immune synapse when incubated on planar lipid bilayers, and to form conjugates with dendritic cells. Secondly, we observed a T-cell extrinsic mechanism whereby repeated stimulation of WT OT-II T-cells with LPS and OVA323-339 pulsed Ptpn22−/− bone marrow derived dendritic cells (BMDCs) was sufficient to enhance Th1 cell development compared to WT BMDCs. Furthermore, this response could be reversed by LFA-1 blockade. Our data point to two related but distinct mechanisms by which PTPN22 regulates LFA-1 dependent signals to enhance Th1 development, highlighting how perturbations to PTPN22 function over time to regulate the balance of the immune response.